Kuwait : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that high oil prices and increased production have enabled the government in Kuwait to continue to record high fiscal and external surpluses and build strong buffers. Overall real non-oil GDP growth is projected to increase modestly to 3 percent in 2013, driven by an increase in domestic consumption and pick-up in public investment. A slight reduction in oil production would bring down total real GDP growth below 1 percent. The overall average consumer price inflation is projected at 3 percent in 2013. The economic outlook is expected to improve further in 2014 and over the medium term.